Conservation status of large mammals in protected and logged forests of the greater Taman Negara Landscape, Peninsular Malaysia - Gopalasamy Reuben Clements; SUSANA ROSTRO-GARCÍA; JAN F. KAMLER; SONG HORNG LIANG; ABDUL KADIR BIN ABU HASHIM (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Clements GR, Rostro-García S, Kamler JF, Liang SH, Hashim AKBA. 2021. Conservation status of large mammals in protected and logged forests of the greater Taman Negara Landscape, Peninsular Malaysia. Biodiversitas 22: 272-277. Peninsular Malaysia contains a large community of IUCN Threatened mammal species, although recent records in some protected areas is unknown. The greater Taman Negara Landscape is one of the national priority areas for tiger conservation, but the recent occurrence of large mammals in the landscape has not been sufficiently updated. Here, we conducted systematic camera-trap surveys in protected and logged forests of the Taman Negara Landscape: Merapoh in Taman Negara National Park (TNM), and the Dungun Timber Complex (DTC), respectively. We found that the diversity of large mammals in TNM appeared to be the same between 2000 and 2016. The detection frequencies (DF) of several Threatened species, such as Malayan tiger (Panthera tigris jacksoni), dhole (Cuon alpinus), and Malayan pangolin (Manis javanica), were similar between surveys, suggesting the relative abundance of these species likely remained stable during the past 16 years. However, the DF of Asian elephant (Elephas maximus) and Malayan tapir (Tapirus indicus) were lower compared to 2000. In DTC, overall mammalian diversity was relatively lower than in TNM, primarily due to the non-detection of two large ungulates: gaur (Bos gaurus) and sambar (Rusa unicolor). Nevertheless, we recorded several other Threatened species of mammals, suggesting there is potential for this forest reserve to preserve some of Peninsular Malaysia’s most Threatened mammal species. Our results suggest that the Taman Negara Landscape is still an important global site for the conservation of several Threatened species, and we recommend an increase in wildlife law enforcement efforts to ensure the survival of its large and diverse mammalian community.